PERSETERUAN IDEOLOGI DALAM DINAMIKA KRITIK HADIS ANTARA MUHAMMAD NASHIRUDDIN AL-ALBANI DAN ABDULLAH AL-GHUMARIY - Rezi, Muhamad; Taufik, Muhammad; Tarihoran, Adlan Sanur; Penmardianto, (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2023)
One of the Takhrij Hadith activists who are phenomenal this century is Muhammad Nashiruddin al-Albani. However, the re-correction of the history with the narrative of the jarh that seemed impolite and against sanad, which was believed to be the ulama, was established and became the point of controversy for other hadith practitioners. There are many Muhadditsin figures who marked al-Albani regarding fiddling with Sanad again. One of them is a Moroccan hadith practitioner, Abdullah al-Ghumariy who is also known for his sauce. At first glance, the ideology and theology of al-Ghumariy and al-Albaniy, are clearly different. al-Ghumariy with his daughter and Tarekat is inversely proportional to al-Albani, a role model of Salafiy, who is aggressively voicing the error and bid'ah of Sufism. In his criticism of al-Albani, especially in Rasâ'il al-Ghumâriyyah, al-Ghumariy can be said to be more focused on the presentation of Sanad criticism carried out by al-Albaniy and there is no editor related to criticism of al-Albaniy's ideology and theology. The focus of the discussion of this paper is how a cross-opinion form correcting the hadith wrapped in ideological and theological differences between al-Albaniy and Abdullah al-Ghumariy.  The method used is the comparative explanation (syarh muqaran) with a character study approach.